Revitalizing Local Moral Teachings: A Study of Islamic Education Values in the Serat Wedhatama and Its Application for Students at Islamic Boarding Schools - Zikri Adib Kurnia; Ahmad Barizi; Muhammad In’am Esha (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Revitalizing Local Moral Teachings: A Study of Islamic Educational Values in the Serat Wedhatama and Its Application for Students at Islamic Boarding SchoolsObjective: This research aims to examine the Islamic education values contained in Serat Wedhatama and its implementation in the learning process at Pondok Pesantren Sunan Drajat Lamongan. Method: The research design employs a case study approach, combining hermeneutic text analysis, observation, and interviews with teachers and students. Results: Serat Wedhatama contains values of faith, worship, and ethics that strengthen students' character. The learning process includes planning, conducting lessons twice a week using drill methods, lectures, and text analysis, followed by evaluation at the end of the session for students who have mastered the material. Conclusion: The existence of local literary works such as Serat Wedhatama is crucial in building character and religious identity for students based on Javanese culture, which remains relevant in modern life. Contribution: This research provides a theoretical foundation for the development of contextual Islamic education grounded in local culture, while also encouraging innovation in digital learning media to expand access and foster character development rooted in local traditions in the digital age.Abstract: Revitalisasi Ajaran Moral Lokal: Kajian Nilai-Nilai Pendidikan Agama Islam dalam Serat Wedhatama dan Pembelajarannya bagi Santri di Pondok PesantrenTujuan: Penelitian ini bertujuan untuk mengkaji nilai-nilai pendidikan agama Islam yang terkandung dalam Serat Wedhatama dan implementasinya dalam pembelajaran di Pondok Pesantren Sunan Drajat Lamongan. Metode: Desain penelitian menggunakan studi kasus, yang menggabungkan analisis hermeneutik teks, observasi, dan wawancara dengan guru dan santri. Hasil: Serat Wedhatama mengandung nilai keimanan, ibadah, dan akhlak yang memperkuat karakter santri. Pembelajaran dilakukan dengan merencanakan, melaksanakan dua kali seminggu menggunakan metode drill, ceramah, dan analisis teks, serta evaluasi di akhir pembelajaran untuk siswa yang telah menguasai materi. Kesimpulan: Keberadaan karya sastra lokal seperti Serat Wedhatama sangat vital dalam membangun karakter dan jati diri keagamaan siswa berbasis budaya Jawa yang relevan dengan kehidupan modern. Kontribusi: Penelitian ini memberikan landasan teori bagi pengembangan pendidikan Islam kontekstual berbasis budaya lokal, sekaligus mendorong inovasi media pembelajaran digital untuk memperluas akses dan memperkuat pengembangan karakter berbasis tradisi lokal di era digital.